2012
DOI: 10.1590/s0103-84782012005000064
|View full text |Cite
|
Sign up to set email alerts
|

Genes termorregulados diferencialmente expressos em Conidiobolus lamprauges

Abstract: RESUMO Conidiobolus lamprauges

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…These fungi are characterized by producing asexual spores, which are relatively large globose (CHAYAKULKEEREE et al, 2006). SILVA et al (2012) also reported that C. lamprauges when exposed to temperature of 37°C overexpresses enolase, suggesting that this enzyme has potential involvement in host-pathogen relationship and virulence of this fungus. GODOY et al (2014) suggest that C. lamprauges produces a range of proteins that are related to thermoregulation triggered by the high temperature of the host.…”
Section: Etiological Agentsmentioning
confidence: 92%
See 1 more Smart Citation
“…These fungi are characterized by producing asexual spores, which are relatively large globose (CHAYAKULKEEREE et al, 2006). SILVA et al (2012) also reported that C. lamprauges when exposed to temperature of 37°C overexpresses enolase, suggesting that this enzyme has potential involvement in host-pathogen relationship and virulence of this fungus. GODOY et al (2014) suggest that C. lamprauges produces a range of proteins that are related to thermoregulation triggered by the high temperature of the host.…”
Section: Etiological Agentsmentioning
confidence: 92%
“…infection (SILVA et al, 2007a). So far, no drug or chemical has been completely effective in the treatment of conidiobolomycosis (RIET-CORREA et al, 2008;KIMURA et al, 2011;SILVA et al, 2012). VALLE et al (2001) proposed a combination of triazoles, itraconazole and fluconazole, in the treatment of rhinomycosis by C. coronatus in humans; however, there are no reports of any effective treatment in sheep.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Recentemente, foi descrito, por meio da técnica de RDA, a expressão diferencial por C. lamprauges do gene que codifi ca a enolase, sendo que a exposição à temperatura elevada (37ºC) possivelmente esteja associada à superexpressão dessa proteína (SILVA et al, 2012).…”
Section: ------------------------------Halo De Crescimento Médio (Mm)unclassified
“…Genes associados à virulência foram estudados na infecção do fungo em insetos (Freimoser et al 2003) e a sua capacidade de termo resistência em diferentes temperaturas (Silva et al 2012, Godoy et al 2014.…”
Section: Introductionunclassified